Vacuum‐Deposited Inorganic Perovskite Memory Arrays with Long‐Term Ambient Stability. Issue 9 (24th May 2019) - Zou, Chen; He, Lijun; Lin, Lih Y.
Abstract : Recently, metal halide perovskites have been widely used and considered as an alternative to oxides or chalcogenides in memory devices due to the high on–off ratio and low operating voltage, as well as ease of fabrication. However, most of the perovskite thin films in previous studies have been deposited by lab‐scale solution‐processed methods. They are not directly applicable to larger‐scale and volume manufacturing, hindering the commercialization of this technology. Herein, the performance of memory devices based on vacuum‐deposited inorganic perovskite (VDIP) is investigated for the first time. The optimized VDIP‐based memory devices exhibit reliable and reproducible resistive switching (RS) behaviors with a high on–off ratio (>100), low set/reset voltage (<2 V), and reversible RS by fast pulse‐voltage operations. Furthermore, the devices show an excellent ambient stability, and no obvious degradation is observed after storage in an ambient condition for 30 days. The memory devices on flexible substrates also show a good mechanical flexibility under a bending stress. In addition, a VDIP memory array with 16 × 16 memory cells on a large‐scale substrate is demonstrated, suggesting the strong potential of the VDIP for high‐density, large‐area storage devices. Abstract : Developments in memory devices are constantly required to keep up with the data volume nowadays. Herein, a memory array based on a vacuum‐deposited inorganic perovskite is demonstrated. The memory array exhibits reliable resistive switching behaviors with an on–off current ratio around 100 and great ambient stability. A proof‐of‐concept data storage device is also demonstrated.